Assessing Physiological and Genetic Evidence for Evolution of Shared Weedy Rice Traits at the Vegetative Growth Stage - Huang, Zhongyun; Rodriguez, Jorge Andres; Matsuo, Rika; Caicedo, Ana L. (Frontiers in Agronomy, 2021)
Weedy rice (Oryza spp.) has successfully adapted to invasion of cultivated rice (O. sativa L.) fields by being a strong competitor from the early vegetative growth stages to crop harvest. While seed shattering and seed dormancy have been shown to contribute to competitiveness at the reproductive stage, much less is known about the traits that could contribute to weedy rice adaptation at the vegetative stage. We examined several growth and physiological traits in five different weedy rice lineages with different ancestral origins, and found that no single vegetative phenotype characterizes all weedy rice. Divergence in growth and physiological traits between weedy rice groups and their putative cultivated ancestors has been limited, suggesting that altered vegetative traits have not been a common path to weed adaptation. There is a lack of convergence in patterns of gene expression in two independent weedy rice lineages, suggesting that there are few shared genetic mechanisms in the evolution of vegetative traits. We conclude that it must not be assumed that all weedy rice groups necessarily have altered vegetative growth or physiological mechanisms compared to their ancestors, that facilitate their invasion of crop fields.